2017
DOI: 10.1177/0269881117704988
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine dysregulation in the prefrontal cortex relates to cognitive deficits in the sub-chronic PCP-model for schizophrenia: A preliminary investigation

Abstract: Rationale: Dopamine dysregulation in the prefrontal cortex (PFC) plays an important role in cognitive dysfunction in schizophrenia. Sub-chronic phencyclidine (scPCP) treatment produces cognitive impairments in rodents and is a thoroughly validated animal model for cognitive deficits in schizophrenia. The aim of our study was to investigate the role of PFC dopamine in scPCP-induced deficits in a cognitive task of relevance to the disorder, novel object recognition (NOR). Methods: Twelve adult female Lister Hood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…This provides an important explanation for the cognitive deficits in scPCP treated animals and a possible target for drug action. This is consistent with our recent in vivo microdialysis work (McLean et al, 2017) in which we observed that vehicle and scPCP-treated rats have the same PFC dopamine basal levels and the same PFC dopamine concentration throughout the 10 min habituation phase, the 10 min acquisition trial and during the 10 min ITI. During the 10 min retention trial, however, vehicle-treated rats show an increase in dopamine levels in the PFC, compared to the basal level, which was abolished by scPCP treatment.…”
Section: Accepted Manuscriptsupporting
confidence: 93%
“…This provides an important explanation for the cognitive deficits in scPCP treated animals and a possible target for drug action. This is consistent with our recent in vivo microdialysis work (McLean et al, 2017) in which we observed that vehicle and scPCP-treated rats have the same PFC dopamine basal levels and the same PFC dopamine concentration throughout the 10 min habituation phase, the 10 min acquisition trial and during the 10 min ITI. During the 10 min retention trial, however, vehicle-treated rats show an increase in dopamine levels in the PFC, compared to the basal level, which was abolished by scPCP treatment.…”
Section: Accepted Manuscriptsupporting
confidence: 93%
“…accompanying cognitive deficiency seen after this treatment (McLean et al, 2017). In this context, the ability of IRL752 to enhance extracellular levels of DA and NA in the PFC but not in (the DA-dominated) striatal and nucleus accumbens areas is particularly noteworthy.…”
Section: Discussionmentioning
confidence: 93%
“…On the basis on the link between mGluR function and dopamine-dependent behaviours (see above), and the evidence to suggest that PCP pretreatment affects glutamate/dopamine interactions (Javitt, 2007;Jentsch et al, 1998a,b;Jentsch & Roth, 1999), the second key question addressed in this study was whether the effects of sub-chronic PCP are mediated through changes in mGluR regulation of dopamine release. Previous studies have shown that impairments in NOR performance following PCP pretreatment are reversed by dopamine D1 receptor (McLean et al, 2009) and D4 receptor (Sood et al, 2011) stimulation, while saline pretreated animals show a significant increase in dopamine utilization during the retention trial compared to PCP counterparts (McLean et al, 2017;Neill et al, 2010), albeit that this effect was seen in the prefrontal cortex rather than NAc.…”
Section: Discussionmentioning
confidence: 88%